The otherness of cyberspace, virtual reality, and hypertext vis-à-vis "the traditional" - İlter, Tu?rul (My University, 2007)
This article engages with the question of the otherness of cyberspace, VR, and hypertext, and how they are distinguished as "new" from "the traditional." It begins by noting how this "new" present is distinguished by familiar binary oppositions like now vs. past and modern vs. traditional which rely on the notion of a new that is uncontaminated by the old. Both our enthusiasm for the singularly liberating nature of this new future as cybertechnophiles, and our Luddite resistance to its singularly fascistic and panoptic encirclement are similarly informed by this binary opposition. The paper then notes how the other in this opposition is a "domestic other." Thus we always-already know what the other is all about. Arguing that if the other were radically other and not "domesticated," one could not give an account of it in this way, the paper concludes that such alterity requires a rethinking of how one knows the other. The difference between this "wild" other and the "domestic" other is not an external difference but is radical; it is at the root. Therefore, our notions of space, reality, and text need to be complicated and rethought to accommodate what they seem to oppose: cyberspace, virtual reality, and hypertext.
Keywords: Alterity; Difference; Spacing; Supplement; Worlding